Just kids - Smith, Patti (Bloomsbury, 2010)
In this memoir, singer-songwriter Patti Smith shares tales of New York City : the denizens of Max's Kansas City, the Hotel Chelsea, Scribner's, Brentano's and Strand bookstores and her new life in Brooklyn with a young man named Robert Mapplethorpe--the man who changed her life with his love, friendship, and genius.